Hyperprogression after immunotherapy in HNC: literature review and our experience - Nerina Denaro (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2018)
<!--[if gte mso 9]> 800x600 <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-IN X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" SemiHidden="true"